Manejo da floresta secundária para produção de mel: alternativa de uso e sustentabilidade sócio-ambiental para agricultores familiares no nordeste paraense - Almeida Júnior, Walter Figueiredo de (Museu Paraense Emílio Goeldi, 2023)
The secondary forest, locally known as "capoeira", can produce a range of products such as wood, firewood, fruits, seeds, medicinal plants and flowers for bees. Through pollen analysis of honeys from the capoeira areas and pollen loads collected by Apis melifera, it is possible to affirm that they have great potential for apicultural production (honey, pollen and propolis). The present work intends to identify the potential of the apicultural flora of the secondary forest in order to make sustainable use of the natural resources of these areas, allowing the generation of income and quality of life for small rural producers. For this purpose, honey samples were collected from apiaries located in the Community of Benjamin Cosntant, Bragança-PA, installed in coppices of different ages. The samples collected from August to October presented a total of 19 pollen types, highlighting among them Mimosa pudica (malícia), Borreria verticillata (vassourinha-de-botão), Hyptis atrorubens (hortelã-do-campo) and Fabaceae Tipo, which are species that contribute to the bees' diet with pollen and nectar for honey production.